Analysis of Formalin Content and Storage Sanitation of Tofu at Inpres Manonda Market, Palu - Alchamdani; Hesti Indriani; Kiki Sanjaya; Adhe Sofyan Anas; Devi Nadila; Riri Suwahyuni Wahid; Sendhy Krisnasari (Tadulako University, 2025)
In 2023, food poisoning cases in Central Sulawesi were recorded at 205 cases, including 30 cases in Palu City, making food safety supervision crucial. One commonly consumed food in Palu City is tofu, with an average consumption of 0.1917 kg per capita per week. However, tofu is easily spoiled and has the potential to contain hazardous food additives such as formaldehyde. Additionally, the sanitation of storage places English: serves to maintain marketed quality safety. The research aims to examine sanitation and formalin levels in tofu storage areas at Manonda Inpres Market, Palu City. Using descriptive methods, the population is permanent tofu sellers at Manonda Inpres Market, with a total of 8 samples. The samples were placed in coded plastic bags and tested at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Tadulako University, for formalin levels relevant to BPOM policy Number 22 of 2023. Sanitation was analyzed through questions and answers and direct observation based on Minister of Health Regulation 2 of 2023. 4 out of 8 samples (50%) tested positive for formalin, which is dangerous if consumed, and 81.25% of sellers have good sanitation. It is hoped that this study can be used as a reference for BPOM, the Health Office, and market managers in organizing vendor locations, conducting routine inspections, and implementing food storage using food-grade and covered containers, thereby continuously improving food safety standards.